PENGARUH LITERASI KEUANGAN DAN FAKTOR DEMOGRAFI TERHADAP PERILAKU PENGELOLAAN KEUANGAN PRIBADI PADA DOSEN-DOSEN FAKULTAS EKONOMI UKIM - Chricela N Joseph (Fakultas Ekonomi dan Bisnis Universitas Pattimura, 2020)
The term financial literacy is the ability of an individual to make decisions in terms of personal financial knowledge. According to Remund (2010) describes five domains of financial literacy namely knowledge of financial concepts, the ability to communicate about financial concepts, the ability to manage finances, the ability to make financial decisions and the confidence to make future plans. 1) Does financial literacy affect the personal financial management behavior of the UKIM faculty of economics? 2) Does income affect the personal financial management behavior of the UKIM faculty of economics? The output of this study is the publication of the results of studies in the National Scientific Journal (with ISSN). In this study the variables to be examined consist of the independent variable (dependent variable), namely capital ownership, dependents and education level, while the dependent variable (independent variable), namely absolute poverty. Time horizon of one stage research (cross sectional). The analysis in this study is the entire lecturer at the UKIM faculty of economics. The research method used in this research is explanatory survey. The population in this study is the whole faculty of economics at UKIM, amounting to 22 people. While the sample in this study is the entire population. Data analysis techniques used in this study are the validity test, reliability test and Chi Square Test.The results of this study indicate that 1) Demographic factors which include income do not affect the financial behavior of the UKIM faculty of economics. 2) Financial literacy has a significant effect on the financial behavior of the UKIM faculty of economicsKeywords: Financial Literacy, Demographic Factors, Financial Management Behavior.